The Convergence of Hate: An Analysis of UCR–NCVS Hate Crime Trends, 2003 to 2020 - Holder, Eaven (Crime & delinquency, 2024)
Questions remain on whether the UCR constitutes a legitimate source for analyzing hate crime. While a handful of studies have attempted to uncover the law enforcement characteristics associated with reporting hate crime, scholars have yet to triangulate official data with other sources, namely the NCVS. In this study, I replicate past UCR-NCVS convergence analyses on hate crime incidents, determining whether these series converge and if they do so across different forms of bias motivation. Using 18 years of data from 2003 through 2020 at a national level, results indicate mixed support for convergence, drawing implications for research and policy.